A new species of the cricket genus, Cacoplistes from Rajasthan, India (Orthoptera: Phalangopsidae: Cachoplistinae:Cachoplistini) - Meena, Ashok Kumar; Swaminathan, Rajamani; Nagar, Rajendra (Zootaxa, 2019)
A new species of the phalangopsid cricket in Cacoplistes subgenus, Laminogryllus, is reported and described as Cacoplistes (Laminogryllus) latioribus sp nov., from Rajasthan, India. Description of the two existing phenotypic forms, brachypterous and macropterous is provided with suitable plates and figures.